A Comparative Analysis of Trust Based Applications in Wireless Sensor Networks - Gupta, Radhika; Sahil Verma, Dr.; Kavita, Dr.; Ial Yadav, Anup (International Journal of Engineering and Technology, 2018)
The wireless sensor network is a type of ad hoc network which is vulnerable to security attacks, specifically insider attacks. In spite of the fact that confidentiality, integrity and authentication helps in forestalling the particular sort of attacks, but they come at an expense. A traditional and evergreen concept of the trust evaluation and management, among the nodes of a network, for communication is a good and effective security measure. Overseeing trust in a distributed wireless sensor network is a challenging task when coordinated effort or participation is must in accomplishing mission and framework objectives. The paper represents a survey of various trust applications which are very helpful for carrying out a secure data transmission in a sensor network. The analysed trust applications malicious attack detection, secure data aggregation, secure node selection and secure routing.